Fostering Tolerance Through the Hidden Curriculum: An Ethnographic Study of Inclusive Education in an Indonesian Islamic Boarding School - Syarifah; Maskuri; Mistar, Junaidi; Anwar, Saiful; Azizah, Nurul (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to explore the design of inclusive education and the strategies for fostering tolerance at Pondok Modern Darussalam Gontor. This Islamic boarding school integrates religious education and social morality. Using a qualitative approach with ethnographic methods, the research involves field observations, in-depth interviews with students, teachers, and caregivers, and documentation of relevant activities. The main theoretical argument of this study is grounded in inclusive education theory, which views education as a tool for creating a more just and inclusive society. It also considers the concept of the hidden curriculum, which posits that social and moral values can be instilled through social activities beyond the formal curriculum. The findings indicate that Pondok Modern Darussalam Gontor has successfully integrated inclusive education across various dimensions of the curriculum, including intracurricular, co-curricular, and extracurricular activities, which emphasize collaboration, respect for differences, and unity. Additionally, the hidden curriculum, applied through social activities such as community service and scouting, plays a crucial role in shaping tolerance among students. This research contributes to the literature on inclusive religious-based education, particularly in the context of Islamic boarding schools, by demonstrating how inclusive and moderate-based education can address social challenges in Indonesia. The limitations of this study lie in its focus on only one pesantren and the perspectives of students and caregivers. Future research is recommended to include other pesantren and perspectives from parents and the surrounding community to provide a more comprehensive understanding of the impact of inclusive education on attitudes of tolerance.